2018
DOI: 10.1177/1081286518810745
|View full text |Cite
|
Sign up to set email alerts
|

From non-local Eringen’s model to fractional elasticity

Abstract: Eringen's model is one of the most popular theories in nonlocal elasticity. It has been applied to many practical situations with the objective of removing the anomalous stress concentrations around geometric shape singularities, which appear when the local modelling is used. Despite the great popularity of Eringen's model in mechanical engineering community, even the most basic questions such as the existence and uniqueness of solutions have been rarely considered in the research literature for this model. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…Another interesting approach related to our investigation, and going from a nonlocal peridynamic framework to a nonlocal fractional situation in the linear case, appears in the recent references [21,32,33]. It is also worth mentioning [14], where the well-posedness for a fractional linearly elastic equation is shown.…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting approach related to our investigation, and going from a nonlocal peridynamic framework to a nonlocal fractional situation in the linear case, appears in the recent references [21,32,33]. It is also worth mentioning [14], where the well-posedness for a fractional linearly elastic equation is shown.…”
Section: Introductionmentioning
confidence: 99%
“…The existence and uniqueness of solutions to three-dimensional wave equation with the Eringen model as a constitutive equation is studied in [36] and it is found that the problem is in general ill-posed in the case of smooth kernels and well posed in the case of singular, nonsmooth kernels. Considering the longitudinal and shear waves propagation in non-local medium, the influence of geometric nonlinearity is investigated in [37].…”
Section: Introductionmentioning
confidence: 99%
“…However, for more complicated material structures such transparent theory is not available; e. g. for practical computational simulations of behaviour of fibrereinforced concrete structures under mechanical loads [39] recommends the "generalized Mazars model" with several heuristic parameters, respecting anisotropy together with different behaviour under tension and pressure like [9] and [40], inspired by [41], [42] and [21]. Fortunately the recent result [43] on the ill-possedness of the nonlocal approach [24], referring to the existence analysis [44], for boundary conditions significant in practical applications is not addressed to our formulation, as explained in [26]. Therefore we are ready to work with σ = A(σ) with values from R 3×3 sym (or its natural modification, as mentioned above) and to compute…”
Section: Nonlocal Damage Factormentioning
confidence: 99%